2011
DOI: 10.1051/0004-6361/201015558
|View full text |Cite
|
Sign up to set email alerts
|

The long-term millimeter activity of active galactic nuclei

Abstract: We analyze the long-term evolution of the fluxes of six active galactic nuclei (AGN) -0923+392, 3C 111, 3C 273, 3C 345, 3C 454.3, and 3C 84 -in the frequency range 80−267 GHz using archival calibration data of the IRAM Plateau de Bure Interferometer. Our dataset spans a long timeline of ≈14 years with 974−3027 flux measurements per source. We find strong (factors ≈2−8) flux variability on timescales of years for all sources. The flux density distributions of five out of six sources show clear signatures of bi-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 53 publications
3
41
1
Order By: Relevance
“…Therefore, we may expect (1) smaller power spectral indices β and (2) observations of broken power-law periodograms at higher frequencies. Trippe et al (2011) showed that the power spectra of six radio bright AGNs at millimeter wavelengths have β ≈ 0.5, which is much smaller than the values we find in this work. However, windowing effects (especially red-noise leak and aliasing) were not taken into consideration then, making it hard to conclude on the general behavior of mm-radio periodograms.…”
Section: Comparison With Other Studiescontrasting
confidence: 86%
“…Therefore, we may expect (1) smaller power spectral indices β and (2) observations of broken power-law periodograms at higher frequencies. Trippe et al (2011) showed that the power spectra of six radio bright AGNs at millimeter wavelengths have β ≈ 0.5, which is much smaller than the values we find in this work. However, windowing effects (especially red-noise leak and aliasing) were not taken into consideration then, making it hard to conclude on the general behavior of mm-radio periodograms.…”
Section: Comparison With Other Studiescontrasting
confidence: 86%
“…According to the unified model of AGN (Urry & Padovani 1995), blazars are AGN whose jet axis is aligned with the line of sight within a few degrees. They are characterised by strong stochastic (red-noise type) variability across the whole electromagnetic spectrum, from γ-rays to the radio domain, on time scales from hours to years (e.g., Trippe et al 2011;Gupta et al 2012;Park & Trippe 2014;Aleksic et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Considering these observations, we checked the literature for such connections to the 2007 X-ray flare in the source. The mm flux reached its minimum in 2004, and since about 2006 this flux has shown high variability (Trippe et al 2011). However, in this case no counterparts of this X-ray flare were noted in either radio or optical bands; moreover, we could find no report on the birth of any radio knot related to this 2007 "orphan" X-ray flare.…”
Section: Discussionmentioning
confidence: 61%